The Birth of Biopolitics - Davidson, Arnold I. author. aut Link
XVII, 368 p.
Keywords: Foucault continues on the theme of his 1978 course by focusing on the study of liberal and neo-liberal forms of government and concentrating in particular on two forms of neo-liberalism: German post-war liberalism and the liberalism of the Chicago School.